Up-regulated microRNA-185-3p inhibits the development of hyperlipidemia in rats - Hua Zhao; Yanbing Li (Kidney & blood pressure research, 2023)
Introduction: MicroRNA (miR)-185-3p functions in multiple cancers, while the underlying function of miR-185-3p in hyperlipidemia remained obscure. This research was conducted to unravel its function in hyperlipidemia development via modulating mastermind-like 1 (MAML1). Methods: The hyperlipidemia rat model was established by feeding with high fat diet. MiR-185-3p and MAML1 levels in hyperlipidemia rats were detected. Adenoviral vectors altering miR-185-3p and MAML1 levels were injected into hyperlipidemia rats to examine the levels of serum lipids, oxidative stress, inflammatory cytokine, lipid accumulation and cellular morphology in liver tissues of hyperlipidemia rats. The targeting relation between miR-185-3p and MAML1 was manifested. Results: MiR-185-3p expressed at a low level while MAML1 expressed at high level in hyperlipidemia rats. MiR-185-3p overexpression or MAML1 silencing reduced levels of serum lipids, mitigated oxidative stress and inflammatory response, relieved lipid accumulation and pathological morphology in liver tissues in hyperlipidemia rats; while up-regulated MAML1 reversed the effects of augmented miR-185-3p in hyperlipidemia rats. Mechanically, miR-185-3p targeted MAML1. Conclusion: Up-regulated miR-185-3p represses hyperlipidemia development via modulating MAML1 expression. This research provides novel therapeutic candidates for the treatment of hyperlipidemia.